Insights on prussian blue analogue cathode material engineered with polypyrrole surface protection layer for aqueous rechargeable zinc metal battery - Puthiyaveetil, Priyanka Pandinhare; Nair, Aathira; Dilwale, Swati; Kurian, Maria; Joshi, Kavita; Kurungot, Sreekumar (Small, 2024)
One of the key intricacies against using Prussian blue analogues (PBAs) in aqueous batteries is their gradual dissolution in aqueous electrolytes, resulting in inadequate cycling stability. Besides, the rate capability of PBAs is limited due to their poor electrical conductivity. To overcome these challenges, it is essential to tune the physical and chemical properties of PBAs at the nano regime without affecting the inherent charge storage properties, especially at high-voltage operating conditions. Through this work, a strategy is demonstrated to enhance the electrochemical performance of vanadium-based PBA (V-PBA) by surface engineering using a conducting polymer nano-skin (V-PBA/PPy) for aqueous zinc metal batteries. The polypyrrole (PPy) nano-skin over the V-PBA nanoparticles acts as an electron percolation path to ameliorate the poor electronic conductivity of the otherwise pristine V-PBA. Interestingly, the V-PBA with an optimized polypyrrole coating (V-PBA/PPy-2) exhibits an enhanced specific capacity (173 mAh g-1 at 0.10 A g-1) than the pristine V-PBA counterpart (80 mAh g-1) and 85% capacity retention up to 500 cycles. The DFT calculation confirms the synergistic interaction between PPy and V-PBA and the presence of PPy favors the adsorption of Zn.
Keywords: aqueous rechargeable zinc metal battery; DFT; polypyrrole coating; Prussian blue analogue; surface protection layer